Health Outcomes in Developing Countries: The Role of Government and Market Institutions - kibria, Md. Golam; Ahmed, Tahsin Tabassum; Smrity, Dilruba Yesmin; Hossain, Md. Sabbir; Hossain, Md. Akter (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2025)
Experts nowadays judge public health status mostly by looking at life expectancy and maternal and infant mortality. As such, this paper assesses human health outcomes in 23 developing nations in relation to public and private health investment, a stable political environment, the efficiency of the government, regulatory quality, education, and the development of financial institutions from the years 2000–2019. This paper employs the panel-corrected standard error (PCSE) strategy developed by Beck and Katz (1995). This technique is applied if the dataset violates the assumptions of serial correlation or autocorrelation and heteroskedasticity. The outcomes confirm that health spending in the public and private sectors, government effectiveness, regulatory quality, education, and financial institutions favor life expectancy while having a detrimental impact on maternal and infant mortality, except primary school enrollment and private spending on health areas. This paper’s findings imply that the authorities should prioritize public and private health sector development, institutional fairness, and financial institutions to strengthen public health outcomes.